The Effectiveness of Principals’ and Teachers’ Roles In Enhancing Learning Management in Secondary Schools - Syaharuddin; Yudin Citriadin; Hazat Usman Mashwani (CV. Doki Course and Training, 2026)
This study aims to systematically review and analyze the effectiveness of principals’ and teachers’ roles in enhancing learning management in secondary schools. Utilizing the Systematic Literature Review (SLR) method, this research examines scholarly articles retrieved from the Dimensions and Scopus databases, published over the past 10 years. The primary focus of the study is to identify the contributions of principals and teachers in improving the quality of learning, including the implementation of educational technology as an innovative strategy. The findings indicate that educational technology offers significant benefits in supporting learning management; however, its success is not uniform. Key factors such as technology design, user acceptance, and applied pedagogical strategies are critical in determining its effectiveness. This study highlights the importance of collaboration between principals and teachers in creating effective learning environments and emphasizes the need for integrated learning management strategies to address challenges in modern education.